Electroretinographic responses that may reflect activity of parvo- and magnocellular post-receptoral visual pathways - Kremers, Jan; Link, Barbara (Journal of Vision, 2008)
The electroretinogram (ERG) is a complex retinal response to visual stimuli that contains receptoral and post-receptoral components. Here, data are presented using stimuli that isolate the responses of L (long wavelength sensitive)- or M (middle wavelength sensitive)- cones or that stimulate the two simultaneously. The data show that at a temporal frequency of 12 Hz, ERG responses are L- to M-cone opponent with little inter-individual variability. Furthermore, the ratio of L- to M-cone-driven response strengths in the ERGs is about unity. These are also properties of the L- and M-cone opponent chromatic channel mediated by parvocellular activity. Similar to the parvocellular-mediated temporal sensitivity, the ERG response is robust to moderate changes in state of cone adaptation. Thus, the 12-Hz ERG shares distinct characteristics with the post-receptoral red-green sensitive parvocellular pathway. At higher temporal frequencies, the responses are not cone opponent, the inter-individual variability is larger, the mean L/M ratio is larger than unity, and the responses change more strongly when the state of cone adaptation is altered. These properties are reminiscent of the magnocellular non-opponent channel. The data suggest that under well-controlled conditions, the ERG can be used to study post-receptoral processes of the visual system.
Keywords: electroretinography; magnocellular; parvocellular; L-cones; M-cones; cone opponency; luminance